Endocrine control of benign prostatic hyperplasia. (18th April 2016) - La Vignera, S.; Condorelli, R. A.; Russo, G. I.; Morgia, G.; Calogero, A. E.
Summary: Benign prostatic hyperplasia (BPH) is the most common benign proliferative disease among aging men. Androgens play a key role in the development and growth of the male genital tract favoring differentiation and proliferation of stromal and epithelial cells of the prostate gland. It is known that growth factors play a crucial role in the cross‐talk between stromal cells and epithelial cells. These factors, mainly secreted by stromal cells, act in an autocrine/paracrine manner to maintain prostate cellular homeostasis. A number of experimental studies support the interdependence between growth factors (IGF, FGF, TGF) and the steroid hormone milieu of the prostate. Alterations of these interactions may alter the balance between proliferation and cell death leading to the development of BPH. The onset of BPH is closely related to an inflammatory microenvironment. Chronic inflammation, which generally follows the acute inflammation because of infectious agents, is favored by hormonal or metabolic abnormalities. However, a close correlation between these mechanisms and metabolic or sexual hormones (androgen/estrogen ratio) alteration has been shown suggesting a key role of hypogonadism in the development of prostate inflammation. This review clear shows that the BPH pathogenesis and the subsequent onset of the lower urinary tract symptoms (LUTS) depends from different etio‐pathogenetic factors whose mechanism of action remains to be evaluated.